Peningkatan Keterampilan Proses Sains Siswa melalui Penerapan Pendekatan Keterampilan Proses Pada Mata Pelajaran IPA Di Kelas V MI - Wati Oviana; Soga Billiyan; Syamsul Bahri (Lembaga Studi Agama dan Masyarakat Aceh (LSAMA), 2021)
The learning process in MIN in general, the learning process carried out is still lacking in supporting student development as a whole that is cognitive, affective, and psychomotor. This is due to the lack of choosing a learning approach that is appropriate to student development, so that students are less active and not directly involved in learning so that it affects the low science process skills possessed by students and the lack of teachers in providing opportunities/space for students to develop science process skills and apply in the science learning process. Based on this, one of the efforts to improve and improve science process skills in learning science is to apply a process skills approach. This study aims to analyze and describe the increase in teacher activity, student activity, and students' science process skills through the process skills approach to the singular and mixed object. This research uses the Classroom Action Research method. The data collection technique uses teacher activity observation sheets, student activities and test to test student process skills. Data analysis uses percentage formulas. Based on data processing research results obtained that in the first cycle, teacher activity (80%) with good categories, student activities (77%) with good categories and student process skills (56.72%) with less skilled categories. Whereas in cycle II there was an increase in teacher activity (92%) in the category of excellent, student activity (92%) in the category of excellent and students' scientific process skills (92.67%) in the highly skilled category. Thus it can be concluded that the process skills approach can improve teacher activity, student activity and student science process skills in science subjects in class V MIN 09 Aceh Timur. Keywords: Process Skills Approach, Science Process Skills. Proses pembelajaran IPA di Sekolah MIN umumnya masih terfokus pada pengembangan kognitif siswa. Sedangkan pengembangan keterampilan proses sains siswa sebagai salah satu tujuan pembelajaran IPA masih sering terabaikan. Salah satu upaya yang dapat dilakukan untuk mendukung peningkatan keterampilan proses sains siswa adalah dengan memilih pendekatan pembelajaran yang berdampak pada pengembangan keterampilan proses sains siswa. Penelitian ini bertujuan untuk mendeskripsikan peningkatan aktivitas guru, aktivitas siswa, dan keterampilan proses sains siswa melalui pendekatan keterampilan proses di kelas V MIN 09 Aceh Timur. Penelitian ini menggunakan metode Penelitian Tindakan Kelas (PTK). Adapun teknik pengumpulan data dengan menggunakan lembar observasi aktivitas guru, aktivitas siswa dan test untuk menguji keterampilan proses siswa. Data dianalisis dengan menggunakan rumus persentase. Berdasarkan pengolahan data hasil penelitian diperoleh bahwa pada siklus I, aktivitas guru (80%) dengan kategori baik, aktivitas siswa (77%) dengan kategori baik dan keterampilan proses siswa (56,72%) dengan katagori cukup terampil. Sedangkan pada siklus II mengalami peningkatan pada aktivitas guru (92%) katagori baik sekali, aktivitas siswa (92%) kaatagori baik sekali dan keterampilan proses sains siswa (92,67%) katagori sangat terampil. Dengan demikian dapat disimpulkan bahwa pendekatan keterampilan proses dapat meningkatkan aktivitas guru, aktivitas siswa dan keterampilan proses sains siswa pada mata pelajaran IPA di kelas V MIN 09 Aceh Timur. Kata Kunci: Pendekatan Keterampilan Proses, Keterampilan Proses Sains